Alternative energy resources : the quest for sustainable energy - Kruger, Paul (John Wiley, 2006)
"As the price of petroleum products increases, the world is scrambling to find a suitable replacement energy source. In this comprehensive primer, Professor Paul Kruger examines energy use throughout history and the exponential expansion of our energy use beginning with the Industrial Revolution through the present day. The book then analyzes the various alternative energy sources available, including renewable energy (hydroelectric, solar, wind, biomass, and geothermal), nuclear, and hydrogen. He addresses each energy source's pros and cons based on our needs, availability, and environmental impact aspects. Finally, Dr. Kruger proposes the use of hydrogen as a fuel to sustain our energy supply produced by appropriate technology mixtures of renewable and nuclear energy."--BOOK JACKET.